Perceptual Uncertainty and Its Monitoring in Visual Snow Syndrome: A Multimodal Framework - Sophie De Beukelaer; Antonia Klein; Christoph J. Schankin (Clinical and Translational Neuroscience)
Neurobehavioral signatures, such as cortical hyperexcitability, thalamo-cortical dysrhythmia, and pulvinar dysfunction, appear to drive the persistent visual misperceptions in Visual Snow Syndrome (VSS). We propose that heightened perceptual uncertainty and impaired metacognitive monitoring perpetuate these disturbances and formalize these processes within different frameworks (predictive coding, signal detection theory, and attentional control). By clarifying these mechanisms, we aim to inform targeted interventions that could address this currently untreatable condition.